Nodule formation potential in forage and grain legumes from rhizobia indigenous to Sancti Spíritus, Cuba - Bécquer, C. J.; Prévost, Danielle (Cuban Journal of Agricultural Science, 2016)
The potential of nodule formation from rhizobia isolated from Centrosema spp. and Stylosanthes viscose was evaluated for its future application in agricultural practice. A nodule collection was made from which rhizobia were isolated, identified and assessed morphoculturally. The number of nodules/plant was measured. The number of effective isolates was determined on inoculating forage and grain legumes. The percentage of effective strains was calculated regarding the total of strains for each macrosymbiont and geographical zone. All isolates formed nodules in Macroptilium atropurpureum. However, the isolates obtained from the legumes of the central zone in Lupinus angustifolius only formed nodules between 14 to 29 % while this value was between 20 to 67 % in those from the southern zone in this species. There was no nodulation in Glycine max. or in Medicago sativa, except with the reference strains used. It is concluded that the effective potential of the inoculated strains in different legumes could have been related to typical biochemical mechanisms of the process of radicular infection, rather than with the plant taxonomy. These results could be used in agricultural practice with the inoculation of forage legumes useful for cattle feeding and of legumes from temperate zones that can be inoculated with isolated rhizobia in tropical zones. Other trials, under semi-controlled conditions, are recommended for selecting the most efficient strains. Key words: Bradyrhizobium, legumes, radicular infection, nodulation